RESEARCH REGARDING THE INTRODUCTION OF A LEAST KNOWN VEGETABLE SPECIES IN CULTURE, - LACZI ENIKŐ; APAHIDEAN ALEXANDRU SILVIU (Journal of Plant Development, 2011)
The research concerning the possibility of cultivating Chinese cabbage (Brassica campestris var. pekinensis) took place in the spring of 2011, in the experimental field which belongs to the Vegetable Growing Department from the University of Agricultural Sciences and Veterinary Medicine from Cluj-Napoca. A collection of varieties and hybrids belonging to this species was established, within which a variety (Granat) and four hybrids (Michihli, Kingdom 80, Nepa F1 and Vitimo F1) were used.During the vegetation period measurements were made regarding the growing and the development of these plants in Transylvanian Tableland specific conditions. The processing of data recorded at harvest shows that the obtained yield varied between 41.00 and 63.15 t/ha, the Vitimo F1 hybrid reaching the highest yield. The obtained yields are satisfying, considering that the culture was an ecological one, no chemical products such as fertilisers or substances for prevention and control of pests and diseases were used.